Pengaruh Inovasi Produk dan Green Marketing Terhadap Minat Beli Konsumen (Studi Kasus Eiger Ecosaivior 45 WS Carrier) - Mochammad Ichsan Ginanjar; Muhammad Syahrul Solehudin; Ferdy Juniarsyah; Lena Susi Susanti; Girvin Fauzan Andriawan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This research is motivated by increasing competition in the outdoor product industry which encourages companies to innovate products and implement green marketing strategies to increase consumer buying interest. This research aims to analyze the influence of product innovation and green marketing on consumer buying interest in the EIGER ECOSAVIOR 45 WS Carrier product. The research method used was a quantitative approach with a purposive sampling technique of 100 respondents in Garut Regency. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The research results show that product innovation has a positive and significant effect on consumer buying interest. Green marketing also has a positive and significant effect on purchasing interest. Simultaneously, product innovation and green marketing contribute to increasing consumer buying interest. These findings confirm that sustainable product innovation and the application of environmentally friendly concepts are important to increase product attractiveness and company competitive advantage in the current competitive outdoor industry.